The Effect of K-W-L Plus Metacognitive Reading Strategy on Tenth Grade Students’ Reading Comprehension and Attitudes - Hamood Almamari, Almutasim (2019)
The present study quasi-experimental study examined the impact of the K-W-L Plus metacognitive reading strategy on tenth grade students’ reading comprehension and attitudes. Two main questions were addressed to accomplish the aim of the study which are: Q.1. What is the impact of K-W-L Plus metacognitive reading strategy on tenth grade students’ reading comprehension? Q.2. What are students’ attitudes toward the use of (K-W-L Plus) metacognitive reading strategy in the experimental group? The sample of the study consisted two intact classes (N=54) and were divided into two experimental group and control group. The experimental group received the K-W-L Plus strategy instruction, while the control group received the conventional reading instruction. Two instruments were implemented to collect data which are pre and post reading comprehension test to measure the students’ reading comprehension and an attitude questionnaire to get their attitudes towards the use of K-W-L Plus reading strategy. The results of the study revealed that implementing the K-W-L Plus metacognitive reading strategy had a positive impact on students’’ reading performance. In addition, the students in the experimental group had a positive attitude towards the application of K-W-L Plus reading strategy. Based on these results, implications and recommendations for further research were put forward.